Knowledge, Attitudes, and Practices Among Hepatitis B Patients in Jakarta, Indonesia: A Cross-Sectional Study - Arkok, Hashem S.; Wahyono, Tri Yunis Miko; Prihartono, Nurhayati Adnan; Aldila, Dipo (UI Scholars Hub, 2026)
Hepatitis B remains a major public health problem in Indonesia. This study assessed the knowledge, attitudes, and practices (KAP) of hepatitis B patients in Jakarta to identify gaps in prevention and control and to explore relationships among KAP components. A cross-sectional study was conducted among 128 patients at a government hospital in South Jakarta, using a structured questionnaire that collected demographic information and assessed knowledge, attitudes, and practices regarding hepatitis B transmission and prevention. Despite moderate knowledge levels, major gaps remained. Only a small proportion (10.9%) correctly identified common symptoms, transmission routes (10.2%), and possible complications (18.8%). Misconceptions about transmission and vaccine safety were common, although attitudes toward early diagnosis and treatment were generally positive. Practices also fell within a moderate range; notably, 46.1% of respondents still shared personal items that could facilitate transmission. Higher education, vaccination, income, and awareness participation were associated with better knowledge, attitudes, and practices. There were positive correlations among knowledge, attitude, and practice scores, indicating that better knowledge may lead to improved behaviors. In conclusion, the study reveals persistent misconceptions and behaviors that continue to place hepatitis B patients at risk, despite generally positive attitudes toward care.